FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENYALURAN KREDIT PERBANKAN (STUDI PADA BANK UMUM SWASTA NASIONAL DEVISA) - Saryadi Saryadi (Jurnal Administrasi Bisnis, 2013)
Problems in this study are based on the phenomenon of not optimal lending and Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and the interest rate of Bank Indonesia Certificates (SBI) to the movement of credit. The population in this study is all Devisa National Private Commercial Bank (BUSND). The number of BUSND in 2012 is 34 banks. This study uses observations from January 2011 to February 2012. The method for data analysis method is factor and path analysis. The factors being predicted to have influence to the ability of banks to credit lending is profit, CAR, KAP, ROA, ROA, Liquidity, LDR, NPL, Deposits, Credit and Interest. Based on the analysis, it can be concluded that the impact of independent variables to the amount of loans are: Profit 1.2%, KAP 0.3%, ROA 0.1%, LDR 30.9%, NPL 1.2%, deposits 72.4%, interest -2.1%, and all variables simultaneously 100%.